Balloon and Stent for Ischemic and Hemorrhagic Stroke: A New Trend for Stroke Prevention and Management - Firas Al-Ali (Frontiers Research Topics, 2015)
In recent years, intracranial endovascular use of Balloon and Stent has grown significantly. This issue will focus primarily on recent advances in the use of these methods today. This discussion will also highlight our improvements in understanding the disease process, and not only relying on devices to treat a patient. Wide-necked intracranial aneurysms (IA) were originally thought to be either untreatable or, at the very least, significantly challenging to treat by endovascular means due to the risk of coil protrusion and possibly parent vessel occlusion. However, this view now outdated, today and we will discuss the significant advancment in different flow diverters. The treatment of post-sub arachnoid hemorrhage vasospasm is mature now, as this issue will highlight. In addition, Intracranial atherosclerosis is still a prominent cause of stroke in various populations worldwide. This issue will summarize the challenges of risk factor modification and secondary stroke prevention by defining optimal methods. We will try to outline a new approach for intracranial angioplasty and stenting for stroke prevention. Finally, despite recent impressive increase recanalization rates in acute ischemic stroke treatment, the clinical improvement rate has remained relatively stable. This article will discuss a new means of improving patient selections using the capillary index score (CIS). The future of our specialty relies heavily on better devices, and on a deeper understanding of the disease process. The future is bright and we have already taken the first successful steps.